2002
DOI: 10.3168/jds.s0022-0302(02)74096-4
|View full text |Cite
|
Sign up to set email alerts
|

Molten Globule Structures in Milk Proteins: Implications for Potential New Structure-Function Relationships

Abstract: Recent advances in the field of protein chemistry have significantly enhanced our understanding of the possible intermediates that may occur during protein folding and unfolding. In particular, studies on alpha-lactalbumin have led to the theory that the molten globule state may be a possible intermediate in the folding of many proteins. The molten globule state is characterized by a somewhat compact structure, a higher degree of hydration and side chain flexibility, a significant amount of native secondary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 27 publications
3
49
0
2
Order By: Relevance
“…Other examples of geodesic structures include hexagonal arrangements of basement membrane proteins (Yurchenco and Schittny, 1990), polyhedral enzyme complexes (Wagenknecht et al, 1991), clathrin-coated transport vesicles (Vigers et al, 1986) and all viral capsids (Caspar, 1980). Biological polymers, such as microfilaments (Schutt et al, 1997), lipid micelles (Butcher and Lamb, 1984;Farrell et al, 2002), and individual proteins, RNA and DNA molecules all have been depicted as prestressed tensegrity structures (Ingber, 1998;Ingber, 2000b;Farell et al, 2002) because at this scale no components 'touch' and, hence, all structural stability must depend on continuous tensional (attractive) forces. For example, in proteins, stiffened peptide elements (e.g.…”
Section: Incorporating Structural Complexity: Multimodularitymentioning
confidence: 99%
“…Other examples of geodesic structures include hexagonal arrangements of basement membrane proteins (Yurchenco and Schittny, 1990), polyhedral enzyme complexes (Wagenknecht et al, 1991), clathrin-coated transport vesicles (Vigers et al, 1986) and all viral capsids (Caspar, 1980). Biological polymers, such as microfilaments (Schutt et al, 1997), lipid micelles (Butcher and Lamb, 1984;Farrell et al, 2002), and individual proteins, RNA and DNA molecules all have been depicted as prestressed tensegrity structures (Ingber, 1998;Ingber, 2000b;Farell et al, 2002) because at this scale no components 'touch' and, hence, all structural stability must depend on continuous tensional (attractive) forces. For example, in proteins, stiffened peptide elements (e.g.…”
Section: Incorporating Structural Complexity: Multimodularitymentioning
confidence: 99%
“…Today, gelation of whey proteins is basically considered as a four-phase process [36] consisting of unfolding of the native structure (I), aggregation of the unfolded protein molecules (II), string formation of the aggregates (III), and linkage of the strings to a three-dimensional network (IV). Partially stable intermediates of the three-dimensional structure of whey proteins, called the "molten globule state", are of particular importance during gelation [16,31]. The formation of heat-induced whey protein gels, mainly due to disulfide bridges and hydrophobic interactions, is irreversible [9,10,36].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that S-casein, and indeed other caseins such as -casein, interact with 'molten globule' states or folding intermediates of proteins. As suggested by others, processing treatments in dairy foods have the potential to transform previously native structures into denatured or partially denatured states and that the presence of these states may either present a problem or offer opportunities for novel foods to be developed [123]. This is where the action of molecular chaperones may play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediately folded states of the apo-form of -lactalbumin provide an ideal model for the investigation of protein folding and unfolding and therefore the action of molecular chaperones when present in solution. The molten globule states of apo--lactalbumin exhibit a relatively compact structure in which a secondary structure is largely preserved, but tertiary structure is lost [123]. A characteristic of these states is that they expose significant amounts of hydrophobicity to solution as a result of their being 'uncovered' from the interior of the previously natively folded protein and it is these exposed hydrophobic areas that appear key to their interaction with molecular chaperones [124,125].…”
Section: S-casein Stabilises Proteins Via Formation Of Soluble High mentioning
confidence: 99%